Negative symptom dimensions and social functioning in Chinese patients with schizophrenia - Gao, Tianqi; Huang, Zetao; Huang, Bingjie; Zhou, Tianhang; Shi, Chuan; Yu, Xin; Pu, Chengcheng (Frontiers in Psychiatry, 2022)
Negative symptoms can seriously affect social functioning in Chinese patients with schizophrenia. However, the role of various components of negative symptoms in social functioning remains unclear. This study aimed to explore the associations among three different dimensions of negative symptoms (i.e., communication, emotion, and motivation) and social functioning to identify potential therapeutic targets. After collecting and analysing data from patients with schizophrenia, we found Social functioning and employment in patients with schizophrenia was significantly related to motivation. Further studies should focus on the deficits in motivation and consider it as a therapeutic target to improve patients’ social functioning.